The ‘MeBox’ Method and the Emotional Effects of Chronic Illness on Travel - Ramanayake, Uditha; Cockburn-Wootten, Cheryl; McIntosh, Alison (Taylor & Francis, 2019)
Within tourism studies, there has been a gap in attempting to understand chronic illness within the context of travel. Researchers examining affective tourism have noted that much of everyday life endeavours to create order through ‘ontological security’ for individuals. In creating this sense of order, positivity and emotional security are emphasised, while taboo issues such as death, pain and chronic illness are ‘bracketed off’. Despite these attempts at bracketing, travel experiences can prompt individuals to reflect on their own mortality, existence and purpose, which in turn may reshape their travel experiences. For senior travellers, chronic illness may be part of their everyday reality, challenging the individual’s sense of self, time and relationships with places, things and people. These topics can be challenging for data collection, because such experiences can be hidden, emotion-laden, difficult to articulate or difficult for others to observe. Researchers have noted the methodological challenges with the use of traditional data tools and have turned to creative visual methods to facilitate and gain deeper understandings of participants’ experiences of chronic illnesses. We used one creative visual tool, the ‘MeBox’ method, to study the hidden aspects of chronic illness and to understand the embodied experience of chronic illness in the context of their travel. The ‘MeBox’ method was created to understand and communicate the participants’ multifaceted experience of chronic illness. The ‘MeBox’ method contributes to tourism scholarship, particularly for sensitive topics, by facilitating the inclusion of participants’ voices to capture their affective travel experiences. This method usefully represents the deeper emotionality of tourists’ lived experience that may have otherwise remained invisible to others.
Keywords: Tourism; Chronic illness; Hospitality; Creative visual research; Elderly; MeBox methodology